Degreening of 'Satsuma Okitsu' tangerine - Santos, L. O. [UNESP]; Durigan, J. F. [UNESP]; Martins, R. N. [UNESP]; Durigan, M. F.B. [UNESP]; Stuchi, E. S. (International Society for Horticultural Science (ISHS), 2012)
Fruit of 'Satsuma Okitsu' tangerine are similar to 'Ponkan', with a maturation period starting in January, and supplying the Brazilian market during the off-season. Fruits of this cultivar have to be harvested with green peel, which is not well accepted by the market. This study aimed to evaluate the degreening of 'Satsuma Okitsu' tangerine using ethephon (2-chloroethyl phosphonic acid). The fruits were harvested with stems when they reached soluble solids:acidity ratio of >7. After selection, the fruits were treated with the Imazalil fungicide (200 ml 100 L-1) for two min and after 24 hours fruits were dipped in different concentrations of ethephon (Ethrel 240): control, 250, 500 and 1000 ppm. The fruits were analyzed every 3 days during 9 days of storage at 18±2°C, 85±5% RH for appearance, weight loss, rind color, soluble solids, acidity and ascorbic acid content. The experiment was conducted as a factorial in a completely randomized design. The treatment with Ethrel provided the best flavedo or rind degreening which made these fruits turn orange with greater intensity and showed good quality during 9 days at 18°C, besides increase in weight loss.
Keywords: Citrus reticulata; Mandarin; Postharvest